2019
DOI: 10.1515/ntrev-2019-0022
|View full text |Cite
|
Sign up to set email alerts
|

A critique on multi-jet electrospinning: State of the art and future outlook

Abstract: This review is devoted to discuss the unique characteristics of multi-jet electrospinning technique, compared to other spinning techniques, and its utilization in spinning of natural as well as synthetic polymers. The advantages and inadequacies of the current commercial chemical spinning methods; namely wet spinning, melt spinning, dry spinning, and electrospinning are discussed. The unconventional applications of electrospinning in textile and non-textile sectors are reported. Special emphasis is devoted to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 37 publications
1
29
0
Order By: Relevance
“…It is also difficult to calculate the optimal arrangement of needles. These issues can be ameliorated by using a needleless process, or employing secondary or auxiliary electrodes [43][44][45][46].…”
Section: Multi-fluid Electrospinning 231 Multi-jet Electrospinningmentioning
confidence: 99%
“…It is also difficult to calculate the optimal arrangement of needles. These issues can be ameliorated by using a needleless process, or employing secondary or auxiliary electrodes [43][44][45][46].…”
Section: Multi-fluid Electrospinning 231 Multi-jet Electrospinningmentioning
confidence: 99%
“…El-Sayed et al have reported that electrospinning is the proper method of spinning of keratinbased composites to produce nano-fibres or nanofibrous mats [84]. About three decades ago, multi-jet electro-spinning systems were adopted to enhance both productivity and cover area of nano-fibres [85].…”
Section: Electro-spun Keratin Nano-fibresmentioning
confidence: 99%
“…2 Electrospinning process can be further developed for mass production of continuous nanofibers of various polymers and composites materials. [3][4][5][6][7] The diameter of electrospun NFs depends on process parameters such as solution properties (viscosity, conductivity and surface tension), ambient conditions (temperature and humidity) and process conditions (solution flow rate, electric voltage, tip-to-collector distance, tip size). 2,[8][9][10] Electrospun NFs have been proposed as a promising component of filter media for high filtration efficiency.…”
Section: Introductionmentioning
confidence: 99%